Indirect ICU Admissions From an Australian Emergency Department: Risk Factors and Outcomes - Daniel McLennan; Cliff Reid; Rhodri Martin; Susannah Olive; Guy Eslick (Emergency Medicine Australasia, 2026)
ABSTRACT Objective Indirect Intensive Care Unit (ICU) admissions, where patients admitted via the Emergency Department (ED) to a non‐critical care ward subsequently require ICU admission, may reflect missed recognition or underestimation of deterioration. This study aimed to: (1) Compare the frequency of indirect ICU admissions in an Australian hospital with international literature. (2) Describe this cohort according to ED care factors, reason for ICU admission, and hospital mortality. Methods Observational cohort study of indirect ICU admissions occurring within 24 h of ED arrival between 1 June 2019 and 31 May 2022. Postoperative ICU admissions were excluded. Data were extracted from electronic medical records by two independent reviewers using a validated Data Collection Template (DCT). Results Of 701 indirect ICU admissions, 148 met inclusion criteria. Indirect admissions accounted for 11.3% of all ED‐to‐ICU admissions. The most common reason for ICU admission was circulatory insufficiency, representing 43% of cases. Approximately half of patients were discussed with or reviewed by a Fellow of the Australasian College for Emergency Medicine (FACEM). 53% had normal observations (44% without supplemental oxygen); 20% were outside normal limits and a further 22% had altered calling criteria. Hospital mortality was 12.8%, higher than that of a reference Australian ICU population. Presentations between midnight and 08:00 were overrepresented. Conclusions Unplanned indirect ICU admissions occurred less frequently than reported internationally but were associated with high in‐hospital mortality. Given their association with adverse outcomes, quality improvement should focus on patients with abnormal vital signs, particularly circulatory insufficiency, and those presenting overnight.